America in the Thirties - Olszowka, John (Book collections on Project MUSE., 2014)
In this new addition to the America in the Twentieth Century series, Sullivan and others present a detailed look into life in America during the 1930s. Beginning with the events leading up to The Great Depression, America in the Thirties presents the themes and events that shaped America during this decade. President Roosevelt's New Deal, the Dust Bowl and life during the Great Depression, domestic life, and America's foreign policy are some of the many issued covered in this highly readable, concise manuscript. Throughout the text, the authors also provide commentary on the role of various societal groups such as women, immigrants, African Americans, Asian Americans, Native Americans, and Latino Americans. The America in the Twentieth Century series presents the major economic, political, social, and cultural milestones of the decades of the twentieth century. Each decade is treated in individual books: thus far, books focusing on 1920s, 1940s, 1950s, 1960s and 1970s have been published. This latest addition to the series, focusing on the tumultuous 1930s, will provide logical links to the previously published books in the series.